Electrical impedance’s effects of flying insects on selectivity of electrical insecticides - Lahouaria Neddar; Samir Flazi (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The history of controlling destructive insects in the twentieth century makes it clear that the difficulties we encounter today in dealing with these types of insects come from our almost total reliance on one single controlling method, namely the use of chemical insecticides. These toxic and suspected carcinogenic products pose a serious threat to agriculture and the environment. However, the possibility of directing researchers in developing a new way considered as more efficient, more selective and less toxic has proved to be possible. The principle of this approach is based on an attractive effect and an electric effect. Nevertheless, the development of a bio and selective electrical system requires taking into account certain parameters involved in the attraction of insects and electrical discharge such as the electrical impedance. The results showed that the threshold at which the insect is disturbed depends on its conductivity.